Individualisme, religion, spiritualité avec Marcel Gauchet :Quels enjeux et quels possibles pour l’éducation ? - Camille Roelens (Éducation et Socialisation)
This article uses the philosophical work of Marcel Gauchet to consider what the contributions of religions to the spiritual dimension to individuation and individualization could be in democratic modernity. One of Gauchet's main theses is what he calls the exit of the religion. Several clarifications on the Gauchetian thought of politics, religion and education are firstly made. Controversies with other contemporary thinkers about religion are discussed (part 1). Then we turn to the potential place and role of spiritualities in a society of individuals (part 2). Such clarification conditions a better understanding of the way education can grasp the spiritual challenge in an autonomous world. Finally, the conditions for enabling this comprehension in the framework of “ french laïcité” are considered (part 3).